BRIDGING KNOWLEDGE GAPS IN ALZHEIMER’S DISEASE: AN AWARENESS CAMPAIGN AMONG UNIVERSITY STUDENTS - Usman Jaffer; Qistina Hani Rahimi; Nur Ain Illani Nasrol; Raja Sofea Saiful Bahri; Anis Nadhirah Baharum; Julyanon Fatimah; Mawaddah Aqmar Mokhtar; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that significantly impacts individuals, their families, and broader communities. Despite increasing global prevalence, misconceptions and limited awareness—particularly among younger populations—often hinder timely detection and intervention. This study aimed to address knowledge gaps and enhance awareness of AD among university students through a tailored campaign. The methodology comprised three phases. First, a site visit to an Alzheimer’s centre facilitated in-depth interviews with care staff and caregivers, providing qualitative insights into daily challenges and priorities for effective intervention. Second, an intervention campaign was devised to address the core issue of inadequate awareness. Infographics focusing on early onset symptoms, prevention strategies, and caregiver support were disseminated both physically on campus and online via social media platforms. Third, the campaign was executed and evaluated using a mixed-methods approach. A closed-ended Google Forms question (“Do you find the information helpful?”) collected quantitative data on campaign usefulness, while an open-ended prompt captured qualitative feedback. The results revealed uniformly positive feedback on the campaign’s clarity and relevance, alongside constructive suggestions for further improvement. The findings underscore the importance of culturally sensitive, multi-format outreach efforts in raising awareness among younger audiences and highlight the potential for scaling similar initiatives to other communities.